2021
DOI: 10.3171/2021.4.peds21123
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy surgery in children under 3 years of age: surgical and developmental outcomes

Abstract: OBJECTIVE Pediatric epilepsy surgery is known to be effective, but early surgery in infancy is not well characterized. Extensive cortical dysplasia, such as hemimegalencephaly, can cause refractory epilepsy shortly after birth, and early surgical intervention is indicated. However, the complication rate of early pediatric surgery is significant. In this study, the authors assessed the risk-benefit balance of early pediatric epilepsy surgery as relates to developmental outcomes. METHODS This is a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…The most prevalent complication was the development of a hydrocephalus in 14.7% of all patients. Iwasaki et al observed a complication rate of 33% (19/57 patients) in patients operated before the age of three years, while Dunkley et al reported a complication rate of 12% in the same age group [62,63]. In older patients, reported complication rates range from six to 10.5% [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prevalent complication was the development of a hydrocephalus in 14.7% of all patients. Iwasaki et al observed a complication rate of 33% (19/57 patients) in patients operated before the age of three years, while Dunkley et al reported a complication rate of 12% in the same age group [62,63]. In older patients, reported complication rates range from six to 10.5% [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of developing a hydrocephalus after hemispherotomy is determined to be as high as 23% in the pediatric age group [67,68]. In particular, anatomic hemispherectomies pose a risk factor [67], but also HME and low body weight [63,69]. Due to the high number of operated infants with HME and low body weight, this could result in an increased risk for infants.…”
Section: Discussionmentioning
confidence: 99%
“…Putative and largely unknown complications of an early intervention should be weighed against the risk of life-long developmental drawbacks of ongoing detrimental epilepsy and/or anticonvulsant therapy. However, early epilepsy surgery in infancy is receiving increased attention (10,11). First results are promising with seizure freedom ranging from 66 to 82.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical Mortality A single death 31 was reported across 8 studies. 8 prestudies/poststudies, 19,22,23,28,29,35,36 combined 180 infants Low Surgical mortality after functional hemispherectomy/hemispherotomy is rare.…”
Section: Functional Hemispherectomy/ Hemispherotomymentioning
confidence: 99%
“…Rates of hydrocephalus ranged from 0% to 33%. (9 prestudies/poststudies, 18,19,20,25,26,31,33,35,36 combined over 96 a )…”
Section: Hydrocephalusmentioning
confidence: 99%